MALDI‐TOF MS for identification of porcine Brachyspira species. (18th November 2013) - Prohaska, S.; Pflüger, V.; Ziegler, D.; Scherrer, S.; Frei, D.; Lehmann, A.; Wittenbrink, M.M.; Huber, H.
<x xml:space="preserve">Abstract</x> Abstract The aim of this study consisted in evaluating MALDI‐TOF MS as a tool for the identification of the genus Brachyspira (B.) and its relevant species for the pig industry. First, a database was created with 30 control strains, and superspectra for five different porcine Brachyspira species were calculated. In a second step, 67 field isolates were investigated using MALDI‐TOF MS, and results were compared to those obtained using nox gene‐based RFLP (reference method) and biochemical tests. Among the 67 field isolates, five different Brachyspira species were detected using nox gene‐based RFLP analysis. MALDI‐TOF MS analysis correctly assigned all isolates to the genus Brachyspira and identified all isolates from B. hyodysenteriae (29/29), B. pilosicoli (11/11), B. intermedia (4/4) and B. innocens (11/11). In terms of B. murdochii, MALDI‐TOF MS assigned one of 12 isolates ambiguously as B. innocens/B. murdochii. The results of this study indicate that MALDI‐TOF MS facilitates the diagnosis of swine dysentery and porcine intestinal spirochaetosis. Significance and Impact of the Study Current methods for the discrimination of pathogenic Brachyspira hyodysenteriae and Brachyspira pilosicoli from Brachyspira species with low pathogenic potential have proven to be laborious and time‐consuming and are therefore not suitable for routine diagnostics. This study describes the evaluation of MALDI‐TOF MS for the identification of different porcine Brachyspira species in routine diagnostic laboratories. The results suggest that MALDI‐TOF MS is an effective method for the identification of porcine Brachyspira spp. and accelerates diagnosis of swine dysentery and porcine intestinal spirochaetosis.